Rebuilding Fiscal Institutions in Postconflict Countries - Bhattacharya, Rina (Occasional Papers; Occasional Paper ;, 2005)
This paper discusses experiences in reestablishing fiscal management in postconflict countries. Building fiscal institutions in postconflict countries essentially entails a three-step process: (1) creating a legal or regulatory framework for fiscal management; (2) establishing or strengthening fiscal authority; and (3) designing appropriate revenue and expenditure policies while simultaneously strengthening revenue administration and public expenditure management. Based on experiences in 14 postconflict countries, the paper reviews the challenges in rebuilding fiscal institutions in these countries, and identifies key priorities in the fiscal area following the cessation of hostilities.